The genus Congestheriella Kobayashi, 1954 (“Conchostraca”, Diplostraca, Afrograptioidea): redescription and new combination to Isaura olsoni Bock from Venezuela and a new species from Argentina (Upper Jurassic) - Gallego, Oscar Florencio (2010)
The genus Congestheriella Kobayashi (Afrograptioidea-Afrograptidae) was erected to Estheriella lualabensis Leriche from the Lualaba Series (Upper Jurassic, Kimmeridgian) from the Congo Democratic Republic (Africa). Until now, Congestheriella was reported from Central Africa and with some doubt from the northeast of Brazil (Lower Cretaceous, Souza Formation). In this work, based on new material, the genus Congestheriella is emended. The species Isaura olsoni Bock, 1953 from the La Quinta Formation (Upper Jurassic) from Venezuela is assigned to this genus, as Congestheriella olsoni nov. comb. Also, Congestheriella rauhuti sp. nov. from the Puesto Almada Member of the Cañadón Asfalto Formation (Upper Jurassic) from Argentina is described. Other South American species could be related with the new ones, as Graptoestheriella brasiliensis (Oliveira), G. fernandoi Cardoso, Graptoestheriella sp. and Estheriina? costai (Cardoso) from the Upper Jurassic to Lower Cretaceous from different Brazilian basins. The new species is compared with the type species. According with its stratigraphic distribution and age, Congestheriella is considered as a potential biomarker for the Upper Jurassic-Lower Cretaceous sedimentary succesions from western Gondwana. Its paleogeographic distribution allows us to propose a biogeographic province including northern South America and Central Africa. Also, different alternative migration routes are proposed for the dispersion across central Africa, northern South America and Patagonia. A hypotethical evolutionary scheme for the Afrograptidae is presented.